Epigenetic regulations as drivers of insecticide resistance and resilience to climate change in arthropod pests - Mogilicherla, Kanakachari; Roy, Amit (Frontiers in Genetics, 2023)
Arthropod pests are remarkably capable of rapidly adapting to novel forms of environmental stress, including insecticides and climate change. The dynamic interplay between epigenetics and genetics explains the largely unexplored reality underlying rapid climatic adaptation and the development of insecticide resistance in insects. Epigenetic regulation modulates gene expression by methylating DNA and acetylating histones that play an essential role in governing insecticide resistance and adaptation to climate change. This review summarises and discusses the significance of recent advances in epigenetic regulation that facilitate phenotypic plasticity in insects and their symbiotic microbes to cope with selection pressure implied by extensive insecticide applications and climate change. We also discuss how epigenetic changes are passed on to multiple generations through sexual recombination, which remains enigmatic. Finally, we explain how these epigenetic signatures can be utilized to manage insecticide resistance and pest resilience to climate change in Anthropocene.